PENGGUNAAN MEDIA SOSIAL INSTAGRAM & TIKTOK NAGITA TRANSPORT DALAM MENINGKATKAN BRAND AWARNESS: PENGGUNAAN MEDIA SOSIAL INSTAGRAM & TIKTOK NAGITA TRANSPORT DALAM MENINGKATKAN BRAND AWARNESS - Aditya, Muhammad Hafizh; Sarjono, Herning Suryo; Sihabbuddin, Sihabbuddin (Solidaritas, 2024)
The research has a background in the current development of business companies, Nagita Transport is a service business company that is still relatively new, and uses Instagram and Tiktok social media to provide brand awareness to its community. aims to analyze the use of Instagram and Tiktok social media carried out by Nagita Transport. and how to increase Brand Awareness through social media Instagram and Tiktok Nagita Transport. According to Nasrullah (2015), the characteristics of social media provide information about Instagram and TikTok social media, as well as the Instagram theory, according to Atmoko (2012), which provides several features that can be used by Instagram users to provide more information to the public. And there is a theory from Chusumastuti regarding the use of Tiktok. Through a qualitative approach, data was collected through observing features and content from Instagram and Tiktok Nagita Transport. as well as making direct observations at the Nagita Trans Utama company office. And conducted an interview with several Instagram and Tiktok followers from Nagita Transport. The research results show that the use of social media provides followers with everything they can remember so that they can remember it well, from the use of Instagram and Tiktok social media within the Nagita Transport company by using the features of each social media, The use of social media on Instagram is: hashtags, location, follow, share, like, comments and mentions as well as photo and video content. For use of social media on TikTok in the form of: hashtags, comments, shares and video content. With the use of social media Instagram and TikTok, it provides brand awareness to the public. So that the public can properly recognize the name, logo, slogan, characteristics of the Nagita Trans Utama Company. Keywords: Social Media, Instagram, Tiktok, Brand Awareness